A restauração ecológica em destaque: Um retrato dos últimos vinte e oito anos de publicações na área - de Oliveira, Renata Evangelista [UNESP]; Engel, Vera Lex [UNESP] (Oecologia Australis, 2011)
The main aspects of restoration, in various ecosystems, are here discussed, by means of a bibliographic analysis of the last twenty-eight years. The main concepts, research themes and target ecosystems are also described.
Ecological restoration: Analysing the last twenty-eight years of publications in this area
Keywords: Concepts and evolution; Ecological restoration; Forest ecosystems restoration